2018
DOI: 10.1063/1.5044463
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping and axial shifting for strongly absorbing particle with single focused TEM00 Gaussian beam

Abstract: We propose and demonstrate a stable three-dimensional trap and manipulation of a micron-sized strongly absorbing particle in pure liquid glycerol by using a single tight focused TEM00 Gaussian beam. We employ a bottom-side bidirectional view observation system to observe the trapped particle. We use the light at 980 nm to trap the absorbing particle and the light at 532 nm to indicate the distribution of the temperature field around the trapped particle. The trapping position of the absorbing particle is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…(a) focusing a TEM 00 (Gaussian) laser beam [46]; (b) focusing the beam with a "flat top" or "top hat", TFT (TEM "flat top") = TEM 00 + TEM 01 *, where TFT is TEM "Flat top", TEM 01 * = TEM 01 + TEM 10 [47] ( Figure 2a); (c) creating a "flat top" beam in the lens focus area, which is one of the most actual optical research topics [48,49].…”
Section: Methods For Converting the Mode Composition Of Laser Radiationmentioning
confidence: 99%
“…(a) focusing a TEM 00 (Gaussian) laser beam [46]; (b) focusing the beam with a "flat top" or "top hat", TFT (TEM "flat top") = TEM 00 + TEM 01 *, where TFT is TEM "Flat top", TEM 01 * = TEM 01 + TEM 10 [47] ( Figure 2a); (c) creating a "flat top" beam in the lens focus area, which is one of the most actual optical research topics [48,49].…”
Section: Methods For Converting the Mode Composition Of Laser Radiationmentioning
confidence: 99%
“…283,284 Yuan and co-workers exploited the Δα photophoretic force to achieve 3D manipulation of a microparticle composed of carbon black and silica in pure liquid glycerol. 285,286 Thermal convection and thermophoresis played an insignificant role in this specific system due to the high thermal conductivity of the particles and special thermodynamic properties of liquid glycerol (Pećlet number and Reynolds number ≪1 while Prandtl number ≫1). Recently, Bargatin and co-workers demonstrated photophoretic levitation of millimeter-sized mylar films with one side coated with carbon nanotubes (Figure 16g).…”
Section: Optothermal Diffusiophoretic Rotorsmentioning
confidence: 99%
“…In addition, photophoretic force induced by the difference of thermal accommodation coefficients (i.e., Δα photophoretic force) can be synergized with the Δ T photophoretic force, optical radiation force, and gravitation force to trigger transversal rotation of micron-sized particles. , Yuan and co-workers exploited the Δα photophoretic force to achieve 3D manipulation of a microparticle composed of carbon black and silica in pure liquid glycerol. , Thermal convection and thermophoresis played an insignificant role in this specific system due to the high thermal conductivity of the particles and special thermodynamic properties of liquid glycerol (Péclet number and Reynolds number ≪1 while Prandtl number ≫1). Recently, Bargatin and co-workers demonstrated photophoretic levitation of millimeter-sized mylar films with one side coated with carbon nanotubes (Figure g) .…”
Section: Photophoretic Manipulationmentioning
confidence: 99%
“…where 𝑑 is the distance from the optical axis to the marginal beam at the output of MO2. Figure 7 plots the behavior between the change in refractive index (x-axis) and the corresponding change in working distance (y-axis), which is equivalent to the change in trap position [21] or to the focus position in a confocal microscope [24]. In addition, Liu reports that the higher the objective NA, the less power is required for a given ∆WD.…”
Section: Refractive Index Testmentioning
confidence: 99%
“…Regarding the influence of an immersion medium in an optical trap, it has previously been reported how the optical excitation of oil can influence the change in the trap focal length [21], and the same effect has been proven by testing immersion oils of different refractive indexes [22]. It has also been reported that by combining a confocal microscope and an optical trap, when using independent laser sources that share the same immersion objective, the change in the optical trap laser power changes the confocal focus position [23,24].…”
Section: Introductionmentioning
confidence: 99%